Pengaruh Konseling Online Terhadap Fenomena Cabin Fever Siswa di SMP Negeri 1 Tanjung Morawa - Nindya Ayu Pristanti; Rahmulyani Rahmulyani; Zuraida Lubis; Miswanto Miswanto (INDONESIAN COUNSELING AND PSYCHOLOGY, 2021)
The study aimed to investigated the effect of online counseling to cabin fever phenomenon of students in SMP Negeri 1 Tanjung Morawa . The research used a q u a n t i t a t iv e m e th o d . T h e ty p e o f t h is r e s e a r c h w a s q u a s i exp e r i m e n ta l w i t h p r e te s t a n d p o s t t e s t design. The data collection technique used a questionnaire of cabin fever scale. The sample of this research was 10 students which was taken by purposive sampling technique. The data analyzed used Wilcoxon test. The result showed that the wilcoxon signed rank test obtained Jcount = 77 and Jtable = 5.Therefore, Jhitung> Jtable . The level of significance for test α=0.05. It could be concluded that there is the effect of the online counseling to cabin fever phenomenon of students in SMP Negeri 1Tanjung Morawa